Free-Space Communication Turbulence Compensation by Optical Phase Conjugation - Junfan Chen; Yang Huang; Rujun Cai; Anrui Zheng; Zhaoxin Yu; Tianshu Wang; Zhi Liu; Shiming Gao (IEEE Photonics Journal)
A new scheme is proposed to mitigate the atmospheric turbulence effect in coherent free-space optical (FSO) communications by employing optical phase conjugation (OPC) to compensate the signal distortion. The compensation performance of the dual-hop FSO transmission link is simulated using the phase screen method for quadrature phase-shift keying (QPSK) signals. The results show that the bite error rate (BER) can be effectively reduced and the OPC correction is tightly affected by the OPC receiving aperture in strong turbulence regimes. The dual-hop FSO link with the OPC correction is experimentally demonstrated in a turbulence-tunable atmospheric cell, where the OPC is achieved by using degenerate four-wave mixing (DFWM) in a 110-m-long highly nonlinear fiber. At the BER of $1 × {10^{ - 3}}$ , the power penalty for dual-hop link with OPC correction decreases about 1.2 dB and 2 dB compared with the single-trip link and the non-compensation dual-hop link. The result demonstrates that the OPC unit can improve the performances of the coherent FSO communication, and it has the potential to be extended to higher-order modulation formats and higher bit rate processing.